The Role of Vitamins in Health of Pregnance Women - Buranova Gulnoza Boymuratovna; Hamzayeva Nargiza Rajabbayevna; Hazratova Hulkar Normurodovna; Norchayev Utkir Toshkentovich (Research Parks Publishing LLC, 2021)
The article is devoted to study the nutrition of pregnant women living in rural areas. At the same time, the theoretical basis of organization of rational nutrition of pregnant women is studied on the basis of an analysis of the literature, which determines the relative status of vitamins in the daily diet, provides appropriate recommendations for correcting existing changes are provided. Based on the above, the scientific basis for the organization of proper nutrition of pregnant women is illustrated.